Peer leadership in UiTM archery team: The relationship between team captain characteristic, behaviours and team performance / Nurul Syazhera Mohd Asmi - Mohd Asmi, Nurul Syazhera (Faculty of Sport Science and Recreation, 2016)
The purpose of this study is i) To examine the relationship of team captain characteristic toward team performance, ii) To examine the relationship of team captain behaviour toward team performance and iii) To examine the impact of personal characteristic and leader behaviour toward team performance. All the 30 archers (N=30) were participate to answered the questionnaire. The result of this study showed that personal characteristic has significant different (P<.01) and has no significant different (P=0.36) in leader behaviour. The resulted also shows that personal characteristic and leader behaviour give an impact to team performance. The results revealed the importance of peer leadership among university student is giving a good impact to the team performance.